Penerapan Motivasi Melalui Mentoring dalam Membangun Kepemimpinan Remaja di Era Digital - Herda, Lusiana; Santosa, Santosa (EDULEAD: Journal of Christian Education and Leadership, 2024)
The digital era has both positive and negative influences on teenagers' self-identity and potential development. Leadership is one of the crucial potentials in teenagers that needs to be nurtured. Mentoring emphasizes the relational aspect between Mentor and Mentee as one of the alternative methods for developing teenagers' potentials. This research aims to describe the implementation of motivation in the mentoring process and to illustrate the impact of motivation provision through mentoring on the development of teenage leadership potential. The research method utilized qualitative methods, with the subjects being teenagers participating in the Future Center program in Ringin Sari Village, Banjar Margo District, Tulang Bawang Regency, Lampung Province. Data collection methods included observation, interviews, and documentation. Based on the research, motivation provision through mentoring, such as encouragement, praise, rewards, and punishment, has an impact on enhancing teenage leadership development in terms of visionary attitude, initiative, proactivity, and integrity. Mentors play a crucial role in building teenagers' leadership potential. Therefore, it is important for Mentors to continuously improve the quality of applying motivational principles in the mentoring process.AbstrakEra digital memberi pengaruh positif dan negatif terhadap identitas diri remaja dan pengembangan potensinya. Kepemimpinan merupakan salah satu potensi remaja yang penting untuk dikembangkan. Mentoring menekankan relational antara Mentor dan Mentee menjadi salah satu alternatif pengembangan potensi remaja. Penelitian ini bertujuan mendeskripsikan penerapan motivasi dalam proses mentoring, dan mendeskripsikan dampak pemberian motivasi melalui mentoring terhadap perkembangan potensi kepemimpinan remaja. Metode penelitian menggunakan metode kualitatif, subjek penelitian yaitu remaja peserta program Future Center di Desa Ringin Sari, Kecamatan Banjar Margo, Kabupaten Tulang Bawang, Provinsi Lampung. Metode pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Berdasarkan penelitian, pemberian motivasi melalui proses mentoring berupa pemberian dorongan, pujian, reward, dan punishment, berdampak terhadap peningkatan perkembangan kepemimpinan remaja ditinjau dalam hal sikap visioner, inisiatif, proaktif, dan integritas remaja. Mentor memiliki peran penting membangun potensi kepemimpinan remaja. Oleh sebab itu penting Mentor terus meningkatkan kualitas dalam menerapkan prinsip-prinsip pemberian motivasi dalam proses mentoring.